Pengaruh Customer Experience dan Kualitas Pelayanan terhadap Keputusan Pembelian Tiket Kereta Api di Stasiun Madiun - Rahma Eka Widiastutik; Joko Samboro; Rizky Kurniawan Murtiyanto (Indo Publishing, 2026)
PT Kereta Api Indonesia (Persero) at Madiun Station continues to improve customer experience and service quality to meet customer expectations and encourage ticket purchase decisions. This study aims to analyze the influence of customer experience and service quality on train ticket purchase decisions at Madiun Station. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to customers who had purchased train tickets at Madiun Station using a purposive sampling technique. The data were analyzed using multiple linear regression analysis. The results indicate that customer experience and service quality have a positive and significant effect on ticket purchase decisions, both partially and simultaneously. Service quality has a more dominant influence than customer experience in encouraging ticket purchase decisions. These findings suggest that improving customer experience and maintaining service quality can strengthen customers’ purchase decisions. Therefore, PT Kereta Api Indonesia (Persero) is expected to continuously enhance service performance and provide positive experiences for its customers.